Beneficial effects of Lactobacillus-fermented black barley on high fat diet-induced fatty liver in rats. Issue 14 (6th June 2021) - Guan, Qi; Ding, Xin-Wen; Zhong, Ling-Yue; Zhu, Chuang; Nie, Pan; Song, Li-Hua
Abstract : A long-term high-fat diet can cause metabolic disorders, which might induce visceral obesity and hepatic steatosis, and increase hepatic oxidative stress. While Lactobacillus fermented black barley could regulate the disorders. Abstract : A long-term high-fat (HF) diet can cause metabolic disorders, which might induce visceral obesity and ectopic triglyceride storage ( e.g., hepatic steatosis), and increase hepatic oxidative stress. Oxidative stress plays a significant role in the development of complications associated with obesity. Fermented whole cereal foods exhibit healthy potential due to their unique phytochemical composition and the presence of probiotics. In the present study, the regular nutrients and phytochemicals of Lactobacillus -fermented black barley ( Hordeum distichum L.) were analyzed. Further, the black barley fermentation broth (1 mL per 100 g BW per d, equivalent to 1 mL per kg BW of daily human intake) was administered orally to the rats fed on a high fat diet (HF). The anti-oxidative activity and hepatic metabolic profile of Lactobacillus -fermented black barley were investigated. The results showed that the fermentation processing significantly increased the contents of polyphenols ( e.g., ferulic acid, etc .), flavonoids ( e.g., flavone, etc .), vitamin B1 and B2, partial mineral elements ( e.g., Ca, etc .), and thymine. Furthermore, compared to the HF-fed only rats, fermented black barley treatment significantly increased the activities of SOD (superoxide dismutase) and GSH-PX (glutathione peroxidase), and decreased the level of TBARS (thiobarbituric acid reactive substances) in serum, the levels of TG (triglyceride), TC (total cholesterol), NEFA (non-esterified fatty acid) in the liver, and the levels of TC, NEFA in the adipose tissue. This suggested the beneficial effects of fermented black barley on ameliorating oxidative stress and hepatic steatosis, which could be attributed to its regulatory role in the hepatic metabolism of glycerophospholipids, nicotinate and nicotinamide, glutathione, and nucleotide, and on the expression of genes related to oxidative stress (Heat shock protein 90 and reactive oxygen species modulator 1).